Battery, battery pack, and vehicle
Patent Information
- Application Number
- CN202610243698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本申请旨在提供一种电池、电池包及车辆,用于解决电池内部可逆锂的净损失,从而导致电池的首次库仑效率、有效放电容量降低的问题
通过将磷酸铁锂和三元材料作为正极活性物质,三元材料包括镍钴锰酸锂、镍钴铝酸锂中的至少一种,利用三元材料在正极预存一部分锂,弥补活性锂的消耗,这部分“富余”的可逆锂离子可以在电池内部迁移,部分补偿磷酸铁锂相或整个电池体系中因副反应造成的永久性锂损耗,从而提升电池的首次库仑效率和放电容量。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This application belongs to the field of new energy technology, specifically relating to a battery, a battery pack, and a vehicle. Background Technology
[0002] With the rapid development of portable electronic devices, wearable devices, and electric vehicles, there is an increasing demand for efficient, safe, and environmentally friendly energy storage systems. Batteries, due to their rechargeability, high energy density, and environmental friendliness, have become an important component of current energy storage technology.
[0003] In batteries, the cathode material is a key component that determines the battery's energy density, safety performance, and cycle life, and lithium iron phosphate is one of the most mature cathode materials currently in commercial use.
[0004] Despite the many advantages of lithium iron phosphate cathode materials, there is still a net loss of reversible lithium inside the battery during practical applications, which leads to a reduction in the battery's initial coulombic efficiency and effective discharge capacity. Summary of the Invention
[0005] This application aims to provide a battery, battery pack, and vehicle to address the problem of net loss of reversible lithium inside the battery, which leads to a reduction in the battery's initial coulombic efficiency and effective discharge capacity.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application propose a battery, the battery including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector; The positive electrode active material layer contains a positive electrode active substance, which includes lithium iron phosphate and ternary materials, and the ternary materials include at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.
[0007] Optionally, the lithium nickel cobalt manganese oxide includes LiNi x Co y Mn z O2, of which 0.8 <x<1,0<y<0.15,0<z<0.2。
[0008] Optionally, the lithium nickel cobalt manganese oxide includes LiNi 0.82 Co 0.12 Mn 0.06 O2, LiNi 0.85 Co 0.10 Mn 0.05 O 2、 LiNi 0.86 Co 0.08 Mn0.06 O2, LiNi 0.88 Co 0.09 Mn 0.03 O2, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 One or more of O2.
[0009] Optionally, the lithium nickel cobalt aluminum oxide includes LiNi a Co b Al c O2, where 0.8≤a≤0.95, 0.01≤b≤0.15, and 0.05≤c≤0.12.
[0010] Optionally, the lithium nickel cobalt aluminum oxide includes LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.85 Co 0.10 Al 0.05 O 2、 LiNi 0.88 Co 0.02 Al 0.10 O 2、 LiNi 0.90 Co 0.05 Al 0.05 O2, LiNi 0.92 Co 0.04 Al 0.04 One or more of O2.
[0011] Optionally, the amount of the ternary material added is 1-5% based on the mass of the positive electrode active material.
[0012] Optionally, the positive electrode sheet may further include a conductive agent and a binder.
[0013] Optionally, the conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene; and / or, The adhesive includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride-hexafluoropropylene.
[0014] Secondly, embodiments of this application provide a battery pack, which includes the aforementioned negative battery.
[0015] Thirdly, embodiments of this application propose a vehicle including the aforementioned battery pack, wherein the battery pack serves as a power supply for the vehicle.
[0016] Compared with existing technologies, the battery described in this application has the following advantages: By using lithium iron phosphate and ternary materials as positive electrode active materials, including at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, a portion of lithium is pre-stored in the positive electrode using ternary materials to compensate for the consumption of active lithium. This "surplus" reversible lithium ions can migrate inside the battery, partially compensating for the permanent lithium loss caused by side reactions in the lithium iron phosphate phase or the entire battery system, thereby improving the battery's initial coulombic efficiency and discharge capacity.
[0017] Meanwhile, lithium iron phosphate can dilute and isolate highly active ternary materials, delaying heat transfer and chain exothermic reactions. When the battery experiences abnormal temperature rise, the lithium iron phosphate phase can absorb some heat, increasing the trigger temperature for thermal runaway of the entire cathode system. In addition, the excellent structural stability and cycle performance of lithium iron phosphate provide skeletal support for the hybrid cathode, inhibiting the structural degradation and particle crack propagation of ternary materials during long-term cycling. Thus, lithium iron phosphate and ternary materials together ensure the safety of the battery during long life cycles and extend cycle life.
[0018] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0019] The embodiments of this application will now be described in detail, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0020] Currently, batteries, due to their outstanding advantages such as excellent charge / discharge repeatability, high energy density, environmental friendliness, and lack of memory effect, have become the core energy storage component of portable electronic devices and wearable devices. Their application scale in new energy vehicles and energy storage systems continues to expand. Among various types of rechargeable batteries, lithium-ion batteries, with their high operating voltage, long cycle life, and low self-discharge rate, have become the most widely used rechargeable battery system. Improving their performance is crucial for promoting the miniaturization, lightweighting, and long-range development of various electrical devices. The cathode material, as the core carrier for lithium-ion insertion / extraction and charge transport in lithium-ion rechargeable batteries, directly determines the battery's energy density, safety performance, and cycle stability, making it a core research direction for optimizing lithium-ion rechargeable battery performance.
[0021] There are many types of cathode materials for lithium-ion secondary batteries. Lithium iron phosphate (LiFePO4) is one of the most mature cathode materials for commercial application. This material has an olivine crystal structure, excellent chemical and thermal stability, and minimal changes in crystal structure during charging and discharging. Moreover, the raw materials are widely available and inexpensive, making it the mainstream choice for portable electronic devices, wearable devices, and power batteries. It occupies an important position in energy storage scenarios with medium to low rate and high safety requirements.
[0022] Despite the numerous advantages of lithium iron phosphate (LFP) cathode materials, several technical challenges remain in practical applications, particularly during the initial charging phase. A solid electrolyte interphase (SEI) film spontaneously forms at the positive and negative electrode interfaces. While this film protects the electrodes and inhibits electrolyte decomposition during subsequent cycles, its formation irreversibly consumes active lithium within the battery system. This results in the conversion of some active lithium into inactive lithium compounds that remain at the interface, leading to a net loss of reversible lithium within the battery. This issue directly results in a low initial coulombic efficiency for LFP lithium-ion rechargeable batteries. Furthermore, the irreversible lithium consumption directly reduces the battery's effective discharge capacity, limiting the further application of LFP in portable electronic devices and wearable devices where higher energy density and initial charge-discharge efficiency are required. Therefore, reducing the irreversible consumption of active lithium and improving initial coulombic efficiency and effective discharge capacity have become key challenges for the optimization and upgrading of LFP cathode materials and corresponding lithium-ion rechargeable batteries.
[0023] This application aims to solve the problem of net loss of reversible lithium inside the battery, which leads to a decrease in the battery's first coulombic efficiency and effective discharge capacity. In one aspect, the embodiments of this application provide a battery, which includes a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive electrode active material layer contains positive electrode active materials, which include lithium iron phosphate and ternary materials. The ternary materials include at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.
[0024] It should be noted that the positive electrode active material layer can be disposed on one surface of the positive electrode current collector, that is, one side, or it can be disposed on both surfaces of the positive electrode current collector, that is, both sides.
[0025] In this embodiment, lithium iron phosphate and ternary materials are used as positive electrode active materials. The ternary materials include at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide. By using the ternary materials to pre-store a portion of lithium in the positive electrode, the consumption of active lithium is compensated. This "surplus" reversible lithium ions can migrate inside the battery, partially compensating for the permanent lithium loss caused by side reactions in the lithium iron phosphate phase or the entire battery system, thereby improving the battery's initial coulombic efficiency and capacity retention.
[0026] Meanwhile, lithium iron phosphate can dilute and isolate the highly active ternary material, retard heat transfer and chain exothermic reactions. When the battery undergoes abnormal temperature rise, the lithium iron phosphate phase can absorb part of the heat, increasing the trigger temperature for thermal runaway of the entire positive electrode system. In addition, the excellent structural stability and cycle performance of lithium iron phosphate provide framework support for the mixed positive electrode, inhibiting the structural deterioration and particle crack propagation of the ternary material during long-term cycles, so that the lithium iron phosphate and the ternary material jointly ensure the safety of the battery during its long life cycle and extend the cycle life.
[0027] In addition, the cost of the ternary material is lower than that of conventional iron-based and nickel-based lithium replenishing agents, which has cost advantages and is easy for industrial large-scale production.
[0028] Alternatively, in one embodiment, lithium nickel cobalt manganese oxide (NCM) includes LiNi x Co y Mn z O₂, where 0.8<x<1, 0<y<0.15, 0<z<0.2.
[0029] It should be noted that x, y, and z respectively represent the molar ratios of nickel, cobalt, and manganese in lithium nickel cobalt manganese oxide. In addition, while satisfying the conditions of 0.8<x<1, 0<y<0.15, and 0<z<0.2, x, y, and z also need to satisfy x+y+z=1.
[0030] It should be noted that 0.8<x<1. For example, x may be one of 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range value formed by any two thereof.
[0031] It should be noted that 0<y<0.15. For example, y may be one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, or a range value formed by any two thereof.
[0032] It should be noted that 0<z<0.2. For example, z may be one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.12, 0.15, 0.18, 0.19, or a range value formed by any two thereof.
[0033] In the embodiments of the present application, nickel serves as the main active site for lithium deintercalation and intercalation. By controlling the molar proportions of nickel, cobalt, and manganese within the ranges of 0.8<x<1, 0<y<0.15, and 0<z<0.2 respectively, the high-nickel, low-cobalt, and low-manganese proportions can effectively improve the discharge capacity of the battery. In the related art, increasing the volumetric energy density of a battery often comes at the cost of rate performance and cycle life. The rate performance and cycle life of the battery of the present application are not adversely affected, and simultaneous improvement of rate performance and cycle life is achieved.
[0034] Optionally, in one embodiment, the lithium nickel cobalt manganese oxide (NCM) includes LiNi 0.82 Co 0.12 Mn 0.06 O2, LiNi 0.85 Co 0.10 Mn 0.05 O 2、 LiNi 0.86 Co 0.08 Mn 0.06 O2, LiNi 0.88 Co 0.09 Mn 0.03 O2, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 one or more of O2.
[0035] It should be noted that in LiNi 0.82 Co 0.12 Mn 0.06 O2, the cobalt proportion is relatively high, the manganese proportion is moderate, the structural stability is optimal, the volume expansion rate during cycling is lower, which provides a better foundation for the long cycle life of the battery, and is suitable for energy storage and commercial vehicle battery scenarios that have high requirements for cycle durability.
[0036] LiNi 0.85 Co 0.10 Mn 0.05 O2, LiNi 0.86 Co 0.08 Mn 0.06 In O2, the ratio of nickel, cobalt and manganese is more balanced, achieving the optimal coordination of discharge capacity, stability and rate performance, taking into account both the rate and cycle performance of the battery, and being suitable for the core scenario of passenger vehicle power batteries.
[0037] LiNi 0.88 Co 0.09 Mn 0.03The nickel content in O2 is further increased, resulting in higher specific capacity. The manganese content is relatively low, but the cobalt content is moderately retained. It balances high capacity with a certain rate mass transfer efficiency, making it suitable for high-end passenger vehicle scenarios where energy density is a priority.
[0038] LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 The precise retention of manganese in O2 can moderately suppress the risk of thermal runaway, making it suitable for the research and development and mass production of next-generation high-endurance power batteries.
[0039] In this embodiment, the ternary material with the above-mentioned nickel-cobalt-manganese lithium oxide ratio is selected. Through the precise gradient ratio of nickel, cobalt, and manganese, the synergistic effect of cobalt and manganese is used to maintain the stability of the layered structure and suppress the risk of thermal runaway. The low cobalt ratio effectively reduces the raw material cost and dependence on cobalt resources. Each ratio is compatible with existing mass production processes, has high industrialization feasibility, and has excellent compatibility with lithium iron phosphate composite systems. As a high-capacity active component of composite cathode, it achieves a synergistic improvement in high safety and long cycle life, and can cover the performance requirements of multiple application scenarios such as power batteries and energy storage batteries.
[0040] Optionally, in one embodiment, lithium nickel cobalt aluminum oxide (NCA) comprises LiNi a Co b Al c O2, where 0.8≤a≤0.95, 0.01≤b≤0.15, and 0.05≤c≤0.12.
[0041] It should be noted that a, b, and c represent the molar percentages of nickel, cobalt, and aluminum in lithium nickel cobalt aluminum oxide, respectively. In addition, a, b, and c must satisfy the conditions 0.8≤a≤0.95, 0.01≤b≤0.15, and 0.05≤c≤0.12, while also satisfying a+b+c=1.
[0042] It should be noted that 0.8≤a≤0.95. For example, a can be a range of values from 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, or any two of them.
[0043] It should be noted that 0.01≤b≤0.15. For example, b can be a range of one or any two of the following: 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, and 0.15.
[0044] It should be noted that 0.05≤c≤0.12. For example, c can be a range of one or any two of the following: 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, and 0.12.
[0045] In this embodiment, by controlling the molar ratios of nickel, cobalt, and aluminum within the ranges of 0.8≤a≤0.95, 0.01≤b≤0.15, and 0.05≤c≤0.12, respectively, the lattice stabilizing effect of aluminum is used to suppress the risk of structural collapse and thermal runaway. The low cobalt ratio ensures structural toughness while reducing raw material costs and dependence on cobalt resources. In related technologies, increasing battery volumetric energy density often comes at the cost of rate performance and cycle life. However, the rate performance and cycle life of the battery in this application are not negatively affected, achieving a simultaneous improvement in both.
[0046] Optionally, in one embodiment, lithium nickel cobalt aluminum oxide (NCA) comprises LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.85 Co 0.10 Al 0.05 O 2、 LiNi 0.88 Co 0.02 Al 0.10 O 2、 LiNi 0.90 Co 0.05 Al 0.05 O2, LiNi 0.92 Co 0.04 Al 0.04 One or more of O2.
[0047] It should be noted that LiNi 0.80 Co 0.15 Al 0.05 O2 has the highest cobalt content, the best structural stability, and outstanding cycle life, making it suitable for high-end commercial vehicle power batteries and large-scale energy storage batteries with high requirements for cycle durability and safety.
[0048] LiNi 0.85 Co 0.10 Al 0.05 O2 has the most balanced nickel-cobalt-aluminum ratio, achieving optimal synergy in capacity, stability, cost, and rate performance, making it suitable for the long-range and daily use needs of conventional high-end passenger vehicles.
[0049] LiNi 0.88 Co 0.02 Al 0.10O2 has low cobalt and high aluminum content, making it the lowest raw material cost and with excellent thermal stability. It is suitable for low-cost, high-energy-density energy storage batteries and economical high-end passenger vehicle batteries.
[0050] LiNi 0.90 Co 0.05 Al 0.05 O2, LiNi 0.92 Co 0.04 Al 0.04 The ultra-high nickel content in O2 makes it a core choice for the next generation of high-range, high-end passenger vehicle power batteries.
[0051] In this embodiment, the ternary material with the above-mentioned nickel-cobalt-aluminum lithium oxide ratio is selected. The synergistic effect of aluminum and cobalt ensures structural and thermal stability. The low cobalt ratio effectively controls raw material costs and conforms to the industry trend of reducing cobalt. The battery rate performance obtained by the above ratio is excellent, has good compatibility with lithium iron phosphate composite system, and is compatible with existing mass production processes, forming differentiated performance focuses. It can be adapted to different high-energy-density battery application scenarios such as high-end commercial vehicles, passenger vehicles, and energy storage batteries.
[0052] Optionally, in one embodiment, the amount of ternary material added is 1 to 5% based on the mass of the positive electrode active material.
[0053] It should be noted that the amount of ternary material added is 1-5%. For example, the amount of ternary material added is one or any two of the following: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.
[0054] In this embodiment, the amount of ternary material added is 1-5%. During the initial formation and charging process, lithium ions are slowly released, and a portion of lithium is pre-stored in the positive electrode, thereby compensating for lithium ion loss during subsequent cycles and improving cycle performance. The high-capacity active sites of a small amount of ternary material slightly increase the overall specific capacity of the positive electrode. Simultaneously, the excellent ion transport characteristics of ternary material form conductive and mass transfer microchannels inside the positive electrode, improving the rate performance of the lithium iron phosphate base. Furthermore, a small amount of ternary material can preferentially form a stable positive electrode electrolyte interface film with the electrolyte, suppressing side reactions on the lithium iron phosphate surface and the consumption of active lithium, ensuring battery cycle life. However, increasing the amount of ternary material added reduces the battery's specific capacity and rate performance. Therefore, an addition amount of 1-5% of ternary material represents the optimal range for maximizing performance gains.
[0055] Alternatively, in one embodiment, the positive electrode further includes a conductive agent and a binder.
[0056] Optionally, in one embodiment, the conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene.
[0057] Optionally, in one embodiment, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0058] It should be noted that conductive graphite / conductive carbon black is the basic conductive phase, which has the characteristics of low cost and easy dispersion. It can fill the tiny gaps between the positive electrode active material particles, build a basic conductive network, and ensure the basic conductivity of the electrode.
[0059] Carbon nanotubes / graphene are highly efficient conductive phases with ultra-high electronic conductivity and aspect ratio (carbon nanotubes) / specific surface area (graphene). They can bridge the gaps between large particles of positive electrode active material to construct a three-dimensional continuous high-efficiency conductive network, significantly reducing the internal resistance of electrode contacts and significantly improving the rate performance of the battery.
[0060] Polyvinylidene fluoride (PVDF, also known as polyvinylidene fluoride) is the mainstream binder for battery cathodes. It has excellent compatibility with cathode active materials and conductive agents, strong adhesion, and good resistance to electrolyte corrosion and electrochemical stability.
[0061] Polytetrafluoroethylene (PTFE) has stronger adhesion, making it especially suitable for high-density electrodes. It can improve the mechanical properties of the electrodes and is often used in combination with PVDF to make up for the shortcomings of PVDF alone in electrode flexibility.
[0062] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is based on PVDF and introduces hexafluoropropylene, which improves the flexibility of the binder and the electrolyte absorption, making the electrode easier to be wetted by the electrolyte, shortening the ion diffusion path, and relieving the volume stress of the electrode during cycling, thereby further improving cycle life. It can be applied to high-end, high-cycle batteries.
[0063] In this embodiment, the conductive agent in the positive electrode sheet can construct a three-dimensional continuous electron-ion conductive network between the positive electrode active material particles, reduce the internal resistance of the electrode sheet, improve the transmission efficiency of electrons and lithium ions, and ensure the full release of battery discharge capacity and optimization of rate performance. The binder can firmly bond the positive electrode active material and the conductive agent and tightly combine them with the positive electrode current collector, ensuring the structural integrity, mechanical stability and formability of the positive electrode sheet, offsetting the volume stress of the positive electrode active material particles during charging and discharging, maintaining the long-term stability of the conductive network, and significantly improving the battery cycle life. The conductive agent and the binder work synergistically to ensure high conductivity of the electrode sheet while achieving high structural strength.
[0064] Alternatively, in one embodiment, the battery further includes a negative electrode and a separator, wherein the negative electrode includes a negative electrode active material.
[0065] Optionally, in one embodiment, the negative electrode active material includes a carbon-based material, the carbon-based material includes one of graphite, amorphous carbon, and carbon nanomaterials, the graphite includes at least one of natural graphite and artificial graphite; the carbon nanomaterials include at least one of graphene, graphene oxide, carbon nanotubes, and carbon fibers.
[0066] Optionally, in one embodiment, the negative electrode active material includes graphite and silicon, and the silicon includes silicon-carbon particles, pure silicon particles, SiO x at least one of (0<x<2) particles.
[0067] Optionally, in one embodiment, the negative electrode active material may further include one of a tin-based material and a titanium-based material. The tin-based material includes at least one of elemental tin, Sn / C, and SnO2 / C; the titanium-based material includes at least one of lithium titanate (LTO), lithium titanate / graphite composite, and lithium titanate / carbon nanotube composite.
[0068] Optionally, in one embodiment, the negative electrode sheet further includes a conductive agent and a binder; the conductive agent includes at least one of conductive graphite, conductive carbon (SP), carbon black, carbon nanotubes, and graphene; the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.
[0069] Optionally, in one embodiment, the battery further includes an electrolyte, and the electrolyte includes a lithium salt, a solvent, and an additive.
[0070] Optionally, in one embodiment, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium perchlorate (LiClO4).
[0071] Optionally, in one embodiment, the solvent includes one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and propylene carbonate (PC).
[0072] Optionally, in one embodiment, the additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), methylene methane disulfonate (MMDS), siloxane-based additives, lithium bis(oxalate)borate, lithium difluorophosphate, lithium difluoro(oxalate)borate, and lithium nitrate.
[0073] In a second aspect, the embodiments of the present application provide a battery pack, and the battery pack includes the battery described above.
[0074] Thirdly, embodiments of this application provide a vehicle including the aforementioned battery pack, which serves as the vehicle's power supply.
[0075] The battery pack and vehicle embodiments described above include the aforementioned battery and achieve the same technical effects. To avoid repetition, they will not be repeated here. For relevant details, please refer to the description of the battery embodiments.
[0076] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0077] The present application will be described in detail below through embodiments.
[0078] Test method: (1) First charge and discharge test: At 25℃, the battery was charged at a constant current rate of 0.05C to the cutoff voltage of 4.25V, and then charged at a constant voltage of 4.25V until the charging cutoff current dropped to 0.01C and then charging was stopped. After standing for 5~10 minutes, the battery was discharged at a constant current rate of 0.33C to the cutoff voltage of 2.0V. The total amount of charge during the discharge process was recorded, and the initial discharge specific capacity (unit: mAh / g) was calculated based on the mass of the positive electrode active material.
[0079] (2) Cyclic performance test: At 25℃, the battery is charged at a constant current rate of 1C to the cutoff voltage of 3.8V, and then charged at a constant voltage of 3.8V until the charging cutoff current drops to 0.01C and then charging is stopped. After standing for 5~10 minutes, the battery is discharged at a constant current rate of 1C to the cutoff voltage of 2.0V, completing one charge-discharge cycle. The cycle test is carried out continuously according to the above procedure. The discharge specific capacity is recorded once every 100 cycles. The ratio of the discharge specific capacity after 100 cycles to the discharge specific capacity of the first cycle is calculated as the capacity retention rate.
[0080] (3) Powder resistance test: The resistivity of the powder material of the positive electrode active material was measured at room temperature using the four-probe method, as detailed below: Gently press the probe onto the sample surface, apply a small current of 1mA using a source meter, record the voltage, calculate the resistance R=V / I, and then calculate the volume resistivity of the material using the formula ρ=R×S / h, where ρ is in Ω. (cm), where: S is the effective conductive area of the sample (unit: cm²). 2 h is the compaction thickness of the sample (unit: cm); the same sample is tested 3 to 5 times at different locations, and the average value is taken as the final powder resistivity test result.
[0081] Example 1 (1) Preparation of positive electrode sheet The positive electrode active material is obtained by uniformly mixing lithium iron phosphate and ternary material, wherein the addition amount of lithium iron phosphate is 97% and the addition amount of ternary material is 3%, and the ternary material is LiNi. 0.85 Co 0.10 Mn 0.05 O2.
[0082] The raw materials are weighed according to the mass ratio of positive electrode active material: conductive agent: binder of 92:5:3, wherein the conductive agent is conductive carbon black and the binder is polyvinylidene fluoride. Then, N-methylpyrrolidone (NMP) is added and mixed evenly to form a positive electrode slurry with a solid content of 60%. The positive electrode slurry is coated on the aluminum foil of the positive electrode current collector, and after drying and rolling, the positive electrode sheet is obtained.
[0083] (2) Preparation of negative electrode sheet Raw materials were weighed according to a mass ratio of negative electrode active material: conductive agent: binder of 96.4:1:2.6, wherein the negative electrode active material is graphite, the conductive agent is conductive carbon black, and the binder is carboxymethyl cellulose. Then, deionized water was added and mixed evenly to form a negative electrode slurry with a solid content of 40%. The negative electrode slurry was coated on the copper foil of the negative electrode current collector, and after drying and rolling, the negative electrode sheet was obtained.
[0084] (3) Battery preparation The above-mentioned positive electrode sheet, 24-micron polypropylene separator, and above-mentioned negative electrode sheet are stacked in sequence, wound up, and tape is attached to the winding end to obtain a bare battery cell. In an argon atmosphere, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1, and then lithium hexafluorophosphate was added at a concentration of 1.0 mol / L to obtain an electrolyte. The bare battery cell is placed into an aluminum casing, dried at 100°C, and then injected with the electrolyte. After vacuum sealing, settling, formation, and shaping, the battery is obtained.
[0085] Example 2 The difference between Example 2 and Example 1 is as follows: In Example 2, the amount of lithium iron phosphate added in step (1) of preparing the positive electrode was adjusted to 95%, and the amount of ternary material added was adjusted to 5%.
[0086] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0087] Example 3 The difference between Example 3 and Example 1 is as follows: In Example 3, the amount of lithium iron phosphate added in the preparation of the positive electrode sheet in step (1) was adjusted to 96%, and the amount of ternary material added was adjusted to 4%.
[0088] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0089] Example 4 The difference between Example 4 and Example 1 is as follows: In Example 4, the amount of lithium iron phosphate added in step (1) of preparing the positive electrode was adjusted to 98%, and the amount of ternary material added was adjusted to 2%.
[0090] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0091] Example 5 The difference between Example 5 and Example 1 is as follows: In Example 5, the amount of lithium iron phosphate added in the preparation of the positive electrode sheet in step (1) was adjusted to 99%, and the amount of ternary material added was adjusted to 1%.
[0092] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0093] Examples 6-10 The difference between Examples 6-10 and Example 1 is that: In Examples 6-10, during the preparation of the positive electrode sheet in step (1), the ternary material was adjusted to LiNi. 0.82 Co 0.12 Mn 0.06 O2, LiNi 0.92 Co 0.03 Mn 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.88 Co 0.02 Al 0.10 O2, LiNi 0.90 Co 0.05 Al 0.05 O2.
[0094] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0095] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: In Comparative Example 1, no ternary materials were added in the preparation of the positive electrode sheet in step (1), and the positive active material was only lithium iron phosphate.
[0096] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0097] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In Comparative Example 2, the amount of lithium iron phosphate added in the preparation of the positive electrode sheet in step (1) was adjusted to 93%, and the amount of ternary material added was adjusted to 7%.
[0098] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0099] The batteries obtained in each embodiment and comparative example were subjected to initial charge-discharge tests, cycle performance tests, and powder resistance tests. The results are shown in Table 1.
[0100] Table 1
[0101] According to the results in Table 1, when the positive electrode active material in this embodiment includes lithium iron phosphate and ternary materials, the capacity retention rate of the battery after 100 cycles is higher than 96%, and the resistivity is higher than 15Ω. cm, while in Comparative Example 1, excluding ternary materials, the battery's capacity retention after 100 cycles was less than 96%, and its resistivity was only 10Ω. cm; In addition, when the amount of ternary material added is in the optimal range of 1~5%, although the resistivity of the battery of Comparative Example 2 (the amount of ternary material added is 7%) is comparable to that of each embodiment, the capacity retention rate of the battery of the embodiment is higher than that of Comparative Example 2 after 100 cycles. It can be seen that when the embodiment of this application uses ternary material and the amount of ternary material added is in the range of 1~5%, the battery obtained can pre-store a part of lithium at the positive electrode to make up for the consumption of active lithium. This part of the "surplus" reversible lithium ions can migrate inside the battery to partially compensate for the permanent lithium loss caused by side reactions in the lithium iron phosphate phase or the entire battery system, thereby improving the battery's first coulombic efficiency, capacity retention rate and cycle life.
[0102] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0103] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.
Claims
1. A battery, characterized in that, The battery includes a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector; The positive electrode active material layer contains a positive electrode active substance, which includes lithium iron phosphate and ternary materials, and the ternary materials include at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.
2. The battery according to claim 1, characterized in that, The lithium nickel cobalt manganese oxide includes LiNi x Co y Mn z O2, of which 0.8 <x<1,0<y<0.15,0<z<0.2。 3. The battery according to claim 2, characterized in that, The lithium nickel cobalt manganese oxide includes LiNi 0.82 Co 0.12 Mn 0.06 O2, LiNi 0.85 Co 0.10 Mn 0.05 O 2、 LiNi 0.86 Co 0.08 Mn 0.06 O2, LiNi 0.88 Co 0.09 Mn 0.03 O2, LiNi 0.90 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 One or more of O2.
4. The battery according to claim 1, characterized in that, The lithium nickel cobalt aluminum oxide includes LiNi a Co b Al c O2, where 0.8≤a≤0.95, 0.01≤b≤0.15, and 0.05≤c≤0.
12.
5. The battery according to claim 4, characterized in that, The lithium nickel cobalt aluminum oxide includes LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.85 Co 0.10 Al 0.05 O 2、 LiNi 0.88 Co 0.02 Al 0.10 O 2、 LiNi 0.90 Co 0.05 Al 0.05 O2, LiNi 0.92 Co 0.04 Al 0.04 One or more of O2.
6. The battery according to any one of claims 1 to 5, characterized in that, The amount of the ternary material added is 1-5% based on the mass of the positive electrode active material.
7. The battery according to any one of claims 1-6, characterized in that, The positive electrode also includes a conductive agent and a binder.
8. The battery according to claim 7, characterized in that, The conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene; and / or, The adhesive includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride-hexafluoropropylene.
9. A battery pack, characterized in that, The battery pack includes the battery as described in any one of claims 1 to 8.
10. A vehicle, characterized in that, The battery pack includes the battery pack of claim 9, which serves as a power supply for the vehicle.
